2017
DOI: 10.1002/tkm2.1069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hachimijiogan on memory impairment induced by beta‐amyloid combined with cerebral ischemia in rats

Abstract: Aim Alzheimer's disease (AD) is a chronic neurodegenerative condition most often found in older people. Cerebrovascular disease is commonly found in patients with AD. Hachimijiogan (HJG) is a herbal medicine commonly used to treat age‐related disease. The aim of this study was therefore to investigate whether HJG could improve memory impairment in rats treated with amyloid‐β protein (Aβ) and cerebral ischemia (Aβ + CI). Methods Rats were prepared by a combination of intracerebroventricular Aβ injection and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, it has been reported that HJG treatment improved cognitive dysfunction in patients with dementia ( Iwasaki et al, 2004 ). Additionally, several studies, including one of our own, have reported that HJG improves cognitive dysfunction in model animals ( Hirokawa et al, 1994 , 1996 ; Moriyama et al, 2017 ). However, further research is needed to confirm the effects of HJG on cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Furthermore, it has been reported that HJG treatment improved cognitive dysfunction in patients with dementia ( Iwasaki et al, 2004 ). Additionally, several studies, including one of our own, have reported that HJG improves cognitive dysfunction in model animals ( Hirokawa et al, 1994 , 1996 ; Moriyama et al, 2017 ). However, further research is needed to confirm the effects of HJG on cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 84%
“…Previously, HJG has been used to treat the symptoms of dysuria and benign prostatic hyperplasia in elderly patients. However, in recent years it has been reported that HJG also improves cognitive function ( Hirokawa et al, 1994 , 1996 ; Iwasaki et al, 2004 ; Moriyama et al, 2017 ). Therefore, we believed it was important to clarify the mechanisms by which HJG improved cognitive function, as this could enable an extension of the therapeutic uses of HJG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 7 ] We recently showed that memory impairment in CI + Aβ rats was ameliorated by HJG administration after ischemia treatment. [ 8 ] Further, we have shown that HJG in vitro exerts a neurotrophic effect via cAMP response element binding protein (CREB) activation, and that HJG ameliorates cognitive dysfunction in dementia model rats via CREB activation. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%